(3TQM Cdajg GHf eGdcs - (3CHh ESMGb EHQGgje HfehSi Hf eMe(B-(3O GddNei GdTGWHis; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3Gddge EfG fMeOc Ydi eG YdeJ CeG HYO aEf HYV ef jLH Ydi ESYGag cGf bO CTGQ Ydi Cf CbjO Ydi CQLhRg GdEeGe GdYdGeI CHj YHO Gddg GHf eGdc GdUZQi hgj GdeSeGg HGdNdGUI s
(3BNQgG (B:s
(3jfJgi HTQM bhd GHf eGdc , ai HGH GdeHJOC hGdNHQ (B: (3hCHQRfg eWdbkG MjK JdG eGdjS eYfGg dg eMUdG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3fSNI ebGHdI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs